POLYPHONIE IM STADTTEXT VON LEMBERG IN DER FRÜHEN NEUZEIT / POLYPHONY IN THE TEXT OF THE CITY OF L᾿VIV / - Woldan, Alois (Prace Polonistyczne, 2021)
The article analyses texts that describe the city of today’s L’viv at the turn of the 17th century, written by Ukrainian, Polish, and German authors in Church Slavonic, Prosta mova, Latin, and German. The names of some of these authors are known (e.g. the Polish Renaissance poet, Sebastian Fabian Klonowic, or the German merchant and traveller, Martin Gruneweg), while others remain anonymous (e.g. the author of a Ukrainian heraldic poem, a “lamentatio” addressed to the Polish king). These texts have some common aspects – they underline the multinationality of the city population as well as different religious denominations of every ethnic group (special attention is given to the Jewish population of the city) – and they represent conflicting points of view regarding privileges of various groups. Thus, the texts serve as an example of polyphony as defined by Mikhail Bakhtin. They combine different voices representing various national ideologies in one complex work, a text of the city of L᾿viv.